2017
DOI: 10.1007/s10549-017-4294-5
|View full text |Cite
|
Sign up to set email alerts
|

High expression of cyclin D1 is associated to high proliferation rate and increased risk of mortality in women with ER-positive but not in ER-negative breast cancers

Abstract: PurposeCyclin D1 has a central role in cell cycle control and is an important component of estrogen regulation of cell cycle progression. We have previously shown that high cyclin D expression is related to aggressive features of ER-positive but not ER-negative breast cancer. The aims of the present study were to validate this differential ER-related effect and furthermore explore the relationship between cyclin D overexpression and CCND1 gene amplification status in a node-negative breast cancer case–control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 65 publications
9
76
0
3
Order By: Relevance
“…CCND1 and CCND2 belong to the D-type cyclin family, which is commonly regarded as a human cancer promoter. The elevation of CCND1 and CCND2 expression was associated with cancer metastasis [18,19,36]. The research performed by the Delmer group demonstrated that CCND2 was overexpressed in chronic B cell malignancies [37].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…CCND1 and CCND2 belong to the D-type cyclin family, which is commonly regarded as a human cancer promoter. The elevation of CCND1 and CCND2 expression was associated with cancer metastasis [18,19,36]. The research performed by the Delmer group demonstrated that CCND2 was overexpressed in chronic B cell malignancies [37].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Defects in colony formation by PIP5Kα knockout were recovered by the WT, and the K88R mutant had a greater colony‐forming ability (Figure I and J). We assessed transcriptional changes in E2F1, CDK1 and CCND1 whose expression levels correlate with increased cell proliferation and are, in general, elevated in various cancers including breast cancer cells . As shown in Figure K, the mRNA expression levels of E2F1, CDK1 and CCND1 were reduced, but conversely, the mRNA levels of the tumour suppressor FOXO3 were increased in the PIP5Kα knockout SKBR3 cells compared to those in non‐targeting control cells.…”
Section: Resultsmentioning
confidence: 99%
“…In breast cancer, there is a close relationship between ER expression and the effect on cyclin D1 expression on cell cycle activation and prognosis. 7 To test whether this is the case also in desmoid tumors, we tested the association between cyclin D1 and proliferation separately in groups defined by ERβ expression. We found no signs of modification of ERβ expression on the association between cyclin D1 and increased proliferation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 activates cyclin‐dependent kinases (Cdk) 4 and 6, which function as a complex in transition from G1 checkpoint to the S phase by phosphorylating the retinoblastoma tumor suppressor protein. ERα upregulates cyclin D1 in breast cancer and thus inhibition of ERα with endocrine agents results in cell cycle arrest . In hormone refractory breast cancer and other cancers, various proliferative pathways may induce cyclin D1 and Cdk 4/6, such as PI3K .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation